2013
DOI: 10.1155/2013/340658
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal Design Study on Factors Affecting the Determination of Common Odors in Water Samples by Headspace Solid-Phase Microextraction Coupled to GC/MS

Abstract: Geosmin and 2-MIB are responsible for the majority of earthy and musty events related to the drinking water. These two odorants have extremely low odor threshold concentrations at ng L−1 level in the water, so a simple and sensitive method for the analysis of such trace levels was developed by headspace solid-phase microextraction coupled to gas chromatography/mass spectrometry. In this study, the orthogonal experiment design L32 (49) was applied to arrange and optimize experimental conditions. The optimum was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…According to our early study [ 16 , 17 ], the HS-SPME/GC-MS was applied to determine the levels of GSM and 2-MIB in water samples, and the optimum conditions for HS-SPME were as follows: temperature of extraction and desorption, 65°C and 260°C, respectively; time of extraction and desorption, 30 min and 5 min, respectively; ionic strength, 25% (w/v); rotation speed, 600 rpm; solution pH, 5.0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our early study [ 16 , 17 ], the HS-SPME/GC-MS was applied to determine the levels of GSM and 2-MIB in water samples, and the optimum conditions for HS-SPME were as follows: temperature of extraction and desorption, 65°C and 260°C, respectively; time of extraction and desorption, 30 min and 5 min, respectively; ionic strength, 25% (w/v); rotation speed, 600 rpm; solution pH, 5.0.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we had conducted this study in 2012, aiming to obtain the basic data of common odorants (GSM and 2-MIB) in environmental waters in Jiangsu province. To be more specific, the headspace solid-phase microextraction coupled to gas chromatography mass spectrometry (HS-SPME/GC-MS) was applied to determine the levels of GSM and 2-MIB in water samples, and this method can be obtained in our early reports [ 16 , 17 ]. In addition, the water samples were collected in detail as follows: firstly, for water sources of tap water, four kinds of water samples were collected respectively from four cities in Jiangsu, including city A (little lakes as the source), city B (the Changjiang River as source), city C (Lake Taihu as source), and city D (underground water as the source); secondly, for conventional treatment process of tap water, including coagulation and sedimentation, filtration, and disinfection, the water samples were collected respectively from above processes; thirdly, for different seasons of water samples, we collected the samples in three periods in Lake Taihu, including the period when a river is at its normal level (November to December), drought period (February to March), and wet season (July to August) when the algae bloom.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the variables are evenly distributed and independently evaluated in an orthogonal array. This method is an efficient and economical multifactor experimental design method that can determine each variable's optimal conditions through limited experiments (Shi, Liu, Deng, & Yang, 2019;Peng et al, 2013). According to the experimental results of a single factor, three groups of data were selected for an orthogonal experiment with three factors and three levels (Significance level a = 0.05).…”
Section: Effect Of Ph On Turbidity and Cod Removalmentioning
confidence: 99%
“…The total peak area of targets was considered as the experimental response and listed in Table S2, ESI. † 39 Different types of eluents were rstly investigated including MeOH, MeOH-H 2 O (90 : 10, v/v), MeOH-H 2 O (60 : 40, v/v), and ACN-H 2 O (90 : 10, v/v). The result indicated that MeOH-H 2 O (60 : 40, v/v) gave the highest desorption efficiency while MeOH was worst among these types of desorption solvents (Fig.…”
Section: Optimization Of Pmme Conditionsmentioning
confidence: 99%